I would walk 500 miles: using travel costs to analyse the market for popular music concerts. Issue 13 (1st September 2016) - Gabe, Todd
ABSTRACT: This article examines the market for live performances of superstar musical artists. Using data on 56 concerts featuring acts such as Steely Dan, Willie Nelson and Def Leppard, we find that concertgoers have a higher willingness to pay for an increase in the artists' top-10 albums than for an additional chart-topping single.